2016
DOI: 10.1007/s12035-016-9973-4
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Changes Associated with the Protective Effects of Angiopoietin-1 During Blood-Brain Barrier Breakdown Post-Injury

Abstract: Blood-brain barrier (BBB) breakdown to plasma proteins leads to vasogenic edema which when diffuse is a life threatening complication in many types of acute brain injury. In our previous studies, early BBB breakdown was associated with increased expression of endothelial caveolin-1α (Cav-1) protein and decreased expression of occludin. In order to attenuate these changes, the effects of intra-cortical angiopoietin-1 (Ang1), a potent anti-permeability factor, on BBB breakdown was assessed in the cold injury mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…± 0.3) mm and extended into cortical layer 4 as a shallow bowl-shaped lesion. Morphological changes in the cortical cold lesions were similar to our previous observations, including the time course of BBB breakdown, angiogenesis, and the inflammatory cell responses [9,27,29,30,31]. On day 0.5, the lesion area showed coagulative necrosis of the neuropil associated with neuronal loss and residual neurons in this area showed varying degrees of degeneration (Figure 1d).…”
Section: Resultssupporting
confidence: 86%
See 2 more Smart Citations
“…± 0.3) mm and extended into cortical layer 4 as a shallow bowl-shaped lesion. Morphological changes in the cortical cold lesions were similar to our previous observations, including the time course of BBB breakdown, angiogenesis, and the inflammatory cell responses [9,27,29,30,31]. On day 0.5, the lesion area showed coagulative necrosis of the neuropil associated with neuronal loss and residual neurons in this area showed varying degrees of degeneration (Figure 1d).…”
Section: Resultssupporting
confidence: 86%
“…The cold-injury model has been utilized extensively to study BBB breakdown, the initiating factor in vasogenic edema using tracers such as Evans blue [32] and horseradish peroxidase (HRP) [27,30] and also by the immunolocalization of extravasated circulating proteins such as serum proteins [27], fibrinogen [33], and fibronectin [8,29,30] through vessels into the surrounding brain. Since all vessels within the lesion do not show BBB breakdown, immunofluorescence allows the identification of vessels leaking proteins while dual labeling allows the localization of a protein of interest in the endothelium of vessels leaking proteins in the same animal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar patterns of endothelial cell activation are noted in cerebral edema, which is also associated with increased permeability of the BBB 45 . There are two main permeability barriers: the basement membrane and the endothelial cell.…”
Section: Discussionsupporting
confidence: 57%
“…Interestingly, Nag et al [99] found only minimal expression of caspase-3 after ANG-1 production by the endothelium following cortical cold injury in rats. Further, Zhao et al [100] suggested that ANG-1 inhibited glycation end product-induced endothelial cell apoptosis.…”
Section: Regulation Of Bbb Function By Astrocyte-derived Factorsmentioning
confidence: 99%